HARMONISASI SOSIAL BUDAYA ANTAR UMAT BERAGAMA DI DESA LOLIBU KECAMATAN LAKUDO KABUPATEN BUTON TENGAH - Muliyono, Muliyono; Taena, La; Aso, La (Universitas Halu Oleo, 2021)
Diversity in Indonesia is a gift from God, including religious differences. This difference sometimes become conflicts in the community, for example the conflict in Poso, Ambon, Wamena and others, but not all different regions always have conflicts. Instead of, it looks safe, peaceful, and harmonious therefore the researcher is interested in examining this diversity. The purpose of this study is to analyze and describe the harmonization of socio-cultural interactions and the causes of socio-cultural interactions in the village of Lolibu. The type of research is descriptive qualitative. The technique of determining informants is by purposive sampling, and the technique of data collection is done by observation participant, indepth interviews, and document studies. Data analysis techniques are done by (1) data reduction, (2) presentation, (3) verification. The results of this study indicate that socio-cultural interaction between religious communities in Lolibu Village, can be described as follows: First, the harmonization of social-cultural interactions between religious communities such as, the existence of regional ties, mutual respect and respect between religious adherents, the harmonization of the birocrate of Lolibu Village. Second, factors that cause of social and cultural interactions between religious communities such as traditional and cultural units, mutual cooperation (Pohamba-hambai), and marriage.Keywords: Harmonization, social, culture, religious people, Lolibu village